An immunohistochemical and ultrastructural study of the ovary of the immature ostrich (Struthio camelus) - Madekurozwa, Mary-Catherine (University of Pretoria, 2013)
Dissertation (MSc(Anatomy and Physiology))--University of Pretoria, 2005.